Elementary School Students’ Mathematical Literacy: A Descriptive Study Based on Cognitive Style in Central Maluku - Nessy Pattimukay; Johannis Takaria; La Suha Ishabu; Chyntia Pasalbessy; Musa Marsel Maipauw; Sherly Latuihamallo (Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the mathematical literacy skills of elementary school students in terms of reflective and impulsive cognitive styles. Mathematical literacy plays a crucial role in helping students understand and apply mathematical concepts in various life situations; however, elementary school students’ achievement in this area remains low. This study employed a descriptive qualitative approach involving 120 students from four elementary schools in Central Maluku Regency, selected through purposive sampling. The research instruments included the Matching Familiar Figures Test (MFFT) to identify cognitive styles, a mathematical literacy test, and interview guide. Data were analyzed interactively through the stages of reduction, presentation, and conclusion drawing. Data reduction was performed on interview transcripts and test answer sheets to identify problem solving strategies, while the literacy test was assessed using an analytical scoring rubric referring to mathematical literacy indicators. The results showed that out of 120 students, 49 students were identified as having a reflective cognitive style and 71 students as having an impulsive cognitive style. Reflevtive students obtained an average mathematical literacy score of 73,7 (SD = 4,6), while impulsive students obtained an average score of 58,1 (SD= 8,9). Qualitatively, reflective students demonstrated better abilities in answer accuraccy, systematic reasoning, and the ability to explain the problem-solving process. In contrast, impulsive students tended to answer quickly but less accurately, with weak conceptual reasoning and difficulty in representing mathematical ideas. These findings highlight the importance of mathematics teaching strategies that differentiate based on students’ cognitive styles to support optimal mathematical literacy development in elementary Schools.